2009
DOI: 10.1177/0164027509333452
|View full text |Cite
|
Sign up to set email alerts
|

Old-Age Wealth in Mexico

Abstract: The authors examined relationships between the wealth of older adults and their early-life decisions regarding investment in human capital, family formation, and work activities in Mexico, using the 2001 Mexican Health and Aging Study. The authors examined correlates of accumulated financial wealth by gender and across three age cohorts: 50 to 59, 60 to 69, and 70 years or older. The authors outline the changing context these cohorts experienced during their lifetimes; describe patterns of net financial worth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In societies where material transfers predominantly flow from adult children to older parents, the value of having highly educated children may be the monetary transfers that also flow upward. In a previous study of wealth among older Mexicans, Wong and DeGraff (2009) found that parents’ wealth was positively associated with the highest education of children and that this association was stronger in more recent cohorts. Although the authors were cautious to avoid making strong causal arguments, the results hint at the increasing importance of education in determining the income potential of adult children and greater monetary assistance to parents (Wong & DeGraff, 2009, p. 11).…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…In societies where material transfers predominantly flow from adult children to older parents, the value of having highly educated children may be the monetary transfers that also flow upward. In a previous study of wealth among older Mexicans, Wong and DeGraff (2009) found that parents’ wealth was positively associated with the highest education of children and that this association was stronger in more recent cohorts. Although the authors were cautious to avoid making strong causal arguments, the results hint at the increasing importance of education in determining the income potential of adult children and greater monetary assistance to parents (Wong & DeGraff, 2009, p. 11).…”
Section: Introductionmentioning
confidence: 84%
“…In a previous study of wealth among older Mexicans, Wong and DeGraff (2009) found that parents’ wealth was positively associated with the highest education of children and that this association was stronger in more recent cohorts. Although the authors were cautious to avoid making strong causal arguments, the results hint at the increasing importance of education in determining the income potential of adult children and greater monetary assistance to parents (Wong & DeGraff, 2009, p. 11). It thus seems likely that in contexts where filial obligation is strong, monetary transfers from well-educated children to parents may be an important mechanisms linking offspring education with parental health.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…We use the life-course perspective to study late-life well being in Mexico, following previous research (see, for example, Settersten, 2003 or Wong and DeGraff, 2009). This approach considers aging as a process, and late-life stocks are the results of lifetime investments.…”
Section: Life-cycle Frameworkmentioning
confidence: 99%
“…In addition, the research has focused largely on men because there tends to be an interest in the long-term effect of work and retirement decisions, and the information on such work-related factors is more available for men. In our previous work (Wong and DeGraff, 2009), we adapted this theoretical perspective to the context of developing countries and aimed to integrate more fully the experience of women. We argued that in order to apply this perspective to the case of Mexico, a country experiencing fast demographic and economic changes, the models not only need to include measures of engagement in the labor force as potential determinants of late-life financial wealth, but also factors that capture structural changes, such as in family formation behavior and human capital investment.…”
Section: Life-cycle Frameworkmentioning
confidence: 99%